Domestication in the Translation of D. Brown’s “The Da Vinci Code” - Aleknavičiūtė, Gintarė (Respectus Philologicus, 2013)
Literary translation is one of the most widely discussed topics in Translation Studies. There are different opinions and approaches to literary translation. On the one hand, some theorists and translators suggest that linguistic aspects such as syntax, lexis, etc., are of great importance to literary translation; one must keep to the rules of the target language without digression from the original meaning, after all. On the other hand, some scholars believe these factors are insignificant, because turning translation into a linguistic exercise undermines the more important textual, cultural, and situational factors (Leonardi 2000). However, the application of Grice’s Cooperative Principle to literary translation allows the mixture of both the linguistic aspects and all that is left beyond the meaning. The study was inspired by Kirsten Malmkjaer, Gideon Toury and Kristina Shaffner’s debate on Norms, Maxims and Conventions in Translation Studies and Pragmatics (Shaffner 1999). The aim of the article is to analyse the Lithuanian translation of D. Brown’s The Da Vinci Code within the framework of Grice’s Cooperative Principle and the strategy of domestication by reviewing domestication and foreignization and introducing Grice’s Cooperative Principle. The research proves that even though it is virtually impossible for a translator to convey the meaning of the source text exactly as it is given, the insufficient use of domestication in the Lithuanian translation of The Da Vinci Code emphasises the presence of the translator and disrupts the ease of reading.
Keywords: Intercultural Translation; Domestication; Foreignization; Gricean Maxims; Functional Equivalence; Coherence and Cohesion; Translator’s Invisibility